Alternativas desde América Latina a una modernidad ajena - Salas Gonzales, Jesús Gerardo (2019)
In its seven chapters, the book proposes a panoramic review of Eurocentrism, geopolitical changes and the knowledge that established it. It exposes the influence of Cartesian thought as a milestone for the break with theocratic and medieval thought. From the cogito ergo sum, the individual is given agency, detached from the divine and distinguished under the duality of reason / subject and object / nature.